Formulasi Dan Evaluasi Fisik Sediaan Suspensi Kombinasi Ekstrak Biji Pepaya (Carica Papaya L.) Dan Umbi Rumput Teki (Cyperus Rotundus L.) Dengan Variasi Konsentrasi Suspending Agent Pga (Pulvis Gummi Arabici) Dan Cmc-Na (Carboxymethylcellulosum Natrium) - Hasty Martha Wijaya; Rifda Naufa Lina (Cendekia Journal of Pharmacy, 2021)
Suspension preparations are made because some of the active substances have a solubility that is practically insoluble in water, but is required in liquid form. Among the medicinal plants that are practically insoluble in water are papaya seeds (Carica papaya L.) and teki grass tubers (Cyperus rotundus L.), so they are made in the form of a suspension to produce stable preparations. Papaya seeds and teki grass tubers are plants that have pharmacological activities as antibacterial, laxative and pancreatic lipase inhibitors. In the suspension formulation of extracts of papaya seeds and teki grass tubers, a combination of suspending agents PGA (pulvis gummi arabici) and CMC-Na (Carboxymethylcellulosum Sodium) was used. PGA at a concentration of less than 10% has a low viscosity so that it can accelerate sedimentation, so PGA is combined with CMC-Na which is a suspending agent that can increase viscosity and can increase suspension stability. The purpose of the study was to determine the effect of the combination of suspending agents PGA and CMC-Na on the physical properties of extracts of papaya seeds and nut grass tubers and to determine what concentration could provide the best physical quality among the four formulas made. Evaluation of physical stability was carried out for 4 weeks after the preparation was made which included organoleptic, homogeneity, pH, density, viscosity, sedimentation volume and redispersion. From the research results, it is known that the concentration of PGA and CMC-Na carboxymethylcellulose affect the physical stability of the suspension